Six-port network as complex ratio measuring unit for wireless communication system - Mohamed Ghazali, Siti Nor Ain (2014)
The demand of wireless communication usage nowadays is exceeded current network application structures. Many researchers are trying to overcome this problem by performing various studies to find new and better solution compared to available products in the market. One of the devices is a six-port network. The concept of six-port network is applied in the invention of Complex Ratio Measuring Unit (CRMU). In this research, the operating frequency from 2 to 6 GHz is chosen due to the compatibility of CRMU with many applications that operated in that frequency range such as Worldwide interoperabiliy for Microwave Access(WiMAX) and Wireless Local Area Network (WLAN). The operation of CRMU implements six-port network mechanism with two inputs, four outputs and one port is terminated to the matched load. The chosen configuration of CRMU is formed by three 3-dB quadrature couplers and one in-phase power divider. These components are designed individually and integrated on Rogers RO4003C substrate. The design of coupler, power divider and CRMU are obtained based on the microstrip slot multilayer technique. This multilayer microstrip-slot technique consists of three conductive layers sandwiched with two substrate layers. The conductive layer on top and bottom layer are broadside-coupled by slotline formed at the middle layer of common ground plane. This technique allows the designed components to be operated in wideband operating frequency. The design of 3-dB quadrature coupler has three-section rectangular-shaped microstrip with and without additional rectangular stub at the top and bottom layer, and slotline at the ground plane.Meanwhile, in-phase power divider design employs the concept of microstrip-to-slot microstriptransition with rectangular or circular stub terminating the transmissionline. These two designed components are then used to form the CRMU. All designs are simulated using CST Microwave Studio for numerical solution of the electromagnetic fields and fabricated using wet etching technique. Their performances are verified via the measurement using a Vector Network Analyser(VNA). The final design of coupler has measured return loss better than 17 dB,coupling of 3 ± 1 dB, isolation better than 18 dB and phase difference of 90º ± 3º.While, the power divider has measured return loss better than 10 dB and output at Port 2 and Port 3 of 3 ± 0.5 dB. The design of CRMU can modulate information signal into any modulation scheme depending on the termination used at the four output ports. For the case of Quadrature Phase Shift Keying (QPSK) modulation, the output port is connected to short or open termination depending on the modulation state. Therefore, the CRMU can act as a modulator in transceiver application of communication system.